On the Information Content of Ldc Secondary Loan Market Prices - Stone, Mark (IMF Working Papers; Working Paper, 1991)
This note examines the impact of measurable and unmeasurable (not correlated with observed aggregates) information on secondary market LDC loan prices. The Institutional Investor country risk ratings are used to construct a proxy for the non-quantifiable information that moves debt market values. Regression results indicate that market participants use both macroeconomic aggregates and unmeasurable information to price LDC loans. This implies that price changes unrelated to observables need not raise concerns regarding price reliability, and, in fact, such price movements may well be conveying important information not quantified elsewhere.